Pathogenetic mechanisms of chronic acquired toxoplasmosis - Kotsyna, S (Annals of Mechnikov’s Institute, 2020)
Introduction. Toxoplasma gondiiis an intracellular protozoan that infects approximately one-third of the world’s population. Infection in human generally occurs through consuming food or drink contaminated with oocysts and tissue cysts from undercooked meat. Although latent infection with Toxoplasma gondii is among the most prevalent of human infections, it has been generally assumed that, except for congenital transmission, it is asymptomatic. Different conditions such as, number of parasite, virulence of the organism, genetic background, sex, and immunological status seem to affect the course of infection The demonstration that Toxoplasma infections can alter behavior, reproductive function in patients has led to a reconsideration of this assumption. During chronic acquired toxoplasmosis (САT) identified the regularities of changes in the ratio of the immune system and the basal levels of sex hormones available informative methods, which made it possible to evaluate the severity of the flow chart and predict treatment outcome without resorting to complex research methods. Found that the host-parasite relationships and clinical manifestations of chronic toxoplasmosis depend largely on protective and adaptive responses and compensatory abilities of the human body. Material & methods. 112 patients attended in the 6 Department of Kharkiv Regional Infectious Diseases Hospital №22 (Department of Medical Parasitology and Tropical Diseases of Kharkiv Medical Academy of Postgraduate Education,) in Kharkiv, Ukraine were enrolled in the study. Forty four patients (39,3±4,6%) were male and sixty eight (60,7±4,6%) were female. The age of the patients was 18 till 72 years. Results & discussion. All of112 CAT patients had subjective clinical symptoms in various combinations: increased fatigue 99,1 ± 0,9%, headache and tiredness 95,5 ± 1,9%, pain in the liver 88,4 ± 3,1%, bitter taste in the mouth 93,8 ± 2,2%, muscle pain 81,3 ± 3,7% and joint pain 69,6 ± 4,3%. Women complained of painful menstruation (57,4 ± 4,7%), irregular menstrual cycle (85,3 ± 3,4%). In the anamnesis of diseases 10,3 ± 2,8% of women had miscarriages and 27,9 ± 4,2% of women had fetal fading. 47,7 ± 4,7% men complained of the decrease in potency.Objective examination: All of 112 CAT patients had lymphadenopathy, 89,3 ± 3,0% patients had subfibryle temperature, 64,3 ± 4,5% of patients had increased sweating, 53.6 ± 4,7% patients had hypertension, increase in liver size was founded in 21,4 ± 3,8% of patients, skin rashes 10,7 ± 3,0%, spleen was enlarged in 66,9 ± 4,4% of patients.Hormonal status: 59 ± 7,4% men have an increased levels of progesterone, 41 ± 7,4% men have an increased levels of estradіol,13 ± 5,1% men have an decreased levels of testosterone. Women22±5,0% have an increased levels of testosterone, women7,0±3,1% have an increased levels of progesterone, 10±3,6% women have an decreased levels of estradіol. Conclusion. The response of host organism to CAT invasion occurs is not the same. It depends on the initial state protective and adaptive capacity of the organism and the liver diseases. This is one of the determining factors of the host-parasite relationship and clinical manifestations of the disease. Prognostic Criterias that determine adaptive-compensatory capacity of the organism in CAT can be basal levels of estradiol, testosterone and progesterone. Physiological differences between men and women play an important role in determining susceptibility to parasitic diseases. The dichotomy in the incidence and severity of many diseases infectious etiology are a strong arguments that the characteristics ofmen’s physiology and characteristics ofwomen’s physiology are the important factors of the determining susceptibility to disease.